Intelligent control and reduce energy consumption of smart street lighting system - Yaichi Mouaadh; Bouchiba Bousmaha; Rebhi Mhamed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Public lighting is one of the criteria for the development of society, in addition to which it is important in human life, as it ensures safety and security during the night, but this may lead to an increase in energy consumption and therefore there is a deficit in energy bills. This research offers a smart street lighting system that has been implemented and tested at pilot site consists of 9 LED lights in order to reduce energy consumption without compromising the security and safety of street users. The developed system control solution relied on combining the effectiveness of the system with reduced installation costs, As soon as the user enters the street, his movement is detected using a motion sensor, so the controller processes this information and raises the intensity of the lighting around the street user’s area, then sends a message via a wireless network to the next controller, which in turn raises the intensity of the lighting, thus increasing the intensity of lighting in front of the user rather than behind. Through experimental results obtained, the system has proven its effectiveness in achieving energy savings up to 50% depending on the use of the smart control scenario.